Understanding the 'USDA Organic' Label - Danielle D. Treadwell; Mickie E. Swisher (EDIS)
HS-1146, a 6-page illustrated fact sheet by Danielle D. Treadwell and Mickie E. Swisher, briefly outlines the history of the USDAs National Organic Program (NOP), summarizes for consumers the benefits of government regulation of organic food products, and provides a guide for interpreting labels on products with organic ingredients. Includes references. Published by the UF Department of Horticultural Sciences, August 2008.